The Effect of Giving Ginger, Lemongrass, Clove Capsules (JaSeKeh) in Helping Reduce Blood Glucose Levels - Masriadi; Abbas, Hasriwiani Habo; Nur Faisa (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Diabetes mellitus is a disease characterized by increased blood glucose levels (hyperglycemia) which occurs due to the body lacking the hormone insulin. According to data from the International Diabetes Federation (IDF), it shows that until 2021 worldwide there are 10.5% (537 million) adults aged 20-79 years suffering from diabetes mellitus and will continue to increase every year. This study aims to determine the effect of giving ginger, lemongrass, clove capsules (JaSeKeh) in helping to reduce blood glucose levels . The type of research is true experiment research Pretest-Posttest Group design . The population of this study was the entire community in the working area of Kassi Kassi Health Center and the research sample was 100 respondents using the purposive sampling method. The results of the study were obtained from data taken by conducting an examination and then conducting a data normality test and analyzing the data using the Wilcoxon test showing the effect of giving ginger, lemongrass, clove capsules (JaSeKeh) in helping to reduce blood glucose levels with p0.000 <0.05. The conclusion in this study is that there is an effect of giving ginger, lemongrass, clove capsules (JaSeKeh) in helping to reduce blood glucose levels in the work area of the Kassi Kassi Health Center, Makassar City, South Sulawesi Keywords: JaSeKeh; Blood Glucose Level; Diabetes Mellitus